Sleep disturbances in children, adolescents, and young adults with severe psychomotor impairment: impact on parental quality of life and sleep. (25th June 2014) - Tietze, Anna L; Zernikow, Boris; Michel, Erik; Blankenburg, Markus
Abstract : Aim: In childhood, severe psychomotor impairment (SPMI) is associated with profound sleep disturbances. With the help of newly developed and validated measures, we systematically assessed how much a child's sleep disturbance affects parental sleep and quality of life (QoL) in this specific patient group. Method: Parents and their children with SPMI were enrolled from three outpatient centers and one in‐patient center in Germany. We administered a set of questionnaires to the parents that addressed their child's sleep quality, the sleep disturbance‐related parental burden, and the impact on both parental sleep and QoL. Additional questionnaires were used to gather data describing our sample group to allow for comparison with published norms. Results: Parents of 214 children, adolescents, and young adults with SPMI (114 males, 100 females; mean age 10y 5mo, SD 5y 6mo, range 0.1–25y) responded to the questionnaire set (response rate of 66%). We found severe impairment of parental health status and QoL. More than 50% of the parents suffered from a sleep disorder (e.g. prolonged sleep latency, shortened sleep duration). Sleep disturbances in children, adolescents, and young adults correlated strongly with parental sleep disturbances, parental impairment of physical and mental functioning, parental social functioning, and parental working ability. Interpretation: Sleep‐related difficulties have a significant sociomedical impact on the parents of children, adolescents, and young adults with complex neurological diseases. Typically, parents are severely affected in various aspects of daily living. There is a need for novel diagnostic and therapeutic approaches that match the complex sociomedical needs of these patients and their families. What this paper adds: Our study depicted that both the quality of sleep and quality of life (i.e. health status, social or professional life) of parents of children with severe psychomotor impairment are profoundly affected. Sleep disturbances and parental burden have a negative impact on each other. This article is commented on by Weiss on page1136 of this issue.